Calcium material special for autoclaved aerated concrete and preparation method thereof
By optimizing mineral components and performing low-temperature calcination in new dry kilns, the problems of unstable quality and high energy consumption in the production of autoclaved aerated concrete are solved, and more efficient utilization and addition of calcium materials are achieved. The performance of gas concrete is improved.
Patent Information
- Application Number
- CN202411660096.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing quicklime used in the production of autoclaved aerated concrete has problems such as unstable quality, large fluctuations in digestion speed and temperature, high production costs and unstable process performance.
A new calcium material is used to optimize mineral components, especially control the content and activity of f-CaO, and perform low-temperature calcination in a new dry kiln to produce clinker that meets the proportion of specific mineral composition.
It improves the utilization rate of calcium raw materials, reduces energy consumption, enhances the uniformity of pore structure of aerated concrete and the mass stability of the blank, and improves production efficiency and resource utilization efficiency.
Smart Images

Figure BDA0005143073070000021 
Figure BDA0005143073070000071 
Figure FDA0005143073060000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cementitious materials, and in particular to a calcium material special for autoclaved aerated concrete and a preparation method thereof. Background Art
[0002] Autoclaved aerated concrete is a lightweight porous silicate product made of calcium materials (quicklime, cement) and silicon materials (quartz sand, river sand, fly ash and silicon-containing tailings, etc.) as basic components, with appropriate amount of gypsum as a regulator, grinding calcium silicon materials into slurry, batching, adding aluminum powder paste and other gas-generating agents, stirring, pouring, pre-curing, cutting, steaming and other processes. It has many advantages such as light weight, heat preservation, fire prevention, sound insulation, and environmental protection. According to incomplete statistics, the amount of autoclaved aerated concrete produced in China using fly ash as silicon materials accounts for about 80% of the total, and the amount of sandstone, river sand and other silicon materials accounts for about 20%. Quicklime and ordinary 42.5R cement are used as calcium raw materials. The amount and proportion of the two materials are determined according to the production situation of the enterprise itself. The proportion of quicklime used by some production enterprises has reached more than 80% of the total amount of quicklime and cement.
[0003] The free calcium oxide content and activity of quicklime mainly depend on the purity of quicklime and the degree of calcination. Most of the quicklime currently supplied for autoclaved aerated concrete production is produced by many uneven traditional kilns, with unstable raw material properties, extensive management, low calcium carbonate decomposition rate, low CaO content, and high production costs. Its digestion rate, digestion temperature, slurry production, and hydration heat release fluctuate greatly, making it easy for aerated concrete to have problems such as slurry pouring, extremely unstable gas expansion, and difficult to grasp and control the hardening of the blank during production, which brings great trouble to the production of enterprises. At a certain temperature, the calcination rate of limestone depends on the particle size of limestone: the larger the particle size, the slower the calcination rate. The decomposition of calcium carbonate in limestone is carried out layer by layer from the surface to the inside. The thermal conductivity of quicklime is smaller than that of limestone. The thicker the lime layer, the worse the thermal conductivity and the longer the heat transfer time; and the more inward the decomposed CO2 is, the more difficult it is to escape, resulting in the formation of quicklime. The CaO crystals gradually increase due to being in a high temperature state for a long time, and the decomposition rate decreases. Even if advanced quicklime production technology is used, there are still problems such as low output, high energy consumption, and unstable quality. The speed of limestone calcination also depends on the particle size of the limestone and the temperature of the limestone surface. Unlike cement clinker production using new dry kilns, the powdered limestone quickly completes the decomposition reaction in the decomposition furnace and pipeline.
[0004] With the technological progress of the aerated concrete industry, it is often necessary to improve production efficiency and reduce production costs in production. Therefore, high-grade cement or cement with faster setting and hardening speed, such as 42.5R and 52.5 silicate cement, is often used, which will increase the cost of raw materials. The minerals that are most beneficial to the process performance in the aerated concrete system are the active calcium in quicklime, silicate minerals and gypsum components in cement. Other admixtures such as inert materials such as limestone and inert slag are not beneficial to the static process of aerated concrete, and will not react in the steam curing process to generate structural minerals such as tobermorite that are beneficial to performance. For this reason, it is necessary to propose a new calcium material system to improve the utilization rate of calcium raw materials and benefit the process production and quality control of aerated concrete. Summary of the invention
[0005] The object of the present invention is to provide a calcium material specially used for autoclaved aerated concrete and a preparation method thereof, so as to at least solve some of the above technical problems.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A calcium material specially used for autoclaved aerated concrete, comprising the following raw materials in the following mass ratios:
[0008]
[0009] The minerals of the calcium material include: f-CaO content of 42-55wt%, The content is 0-3wt%, the sum of C2S and C3S is 22-45wt%, the sum of C3A and C4AF is 5-20wt%, the content of periclase is 0-1.5wt%, the content of gypsum is 0-2wt%, and the content of other impurity minerals is 0-6wt%; wherein, represents sulfur; S represents silicon.
[0010] The other impurity minerals include perovskite, quartz, calcite and potassium aluminate.
[0011] Furthermore, the iron raw material is at least one of non-ferrous metal ash, copper slag, iron tailings, iron ore, blast furnace slag, and sulfuric acid slag.
[0012] Furthermore, the gypsum is at least one of dihydrate gypsum, anhydrite, desulfurized gypsum, phosphogypsum, and desulfurized ash.
[0013] Furthermore, the siliceous and aluminous material is at least one of low-grade bauxite, aluminum smelting waste slag, aluminum tailings, and fly ash.
[0014] A method for preparing a special calcium material for autoclaved aerated concrete comprises the following steps:
[0015] S1. crush limestone, iron raw material, gypsum and silicon-aluminum material respectively for standby use;
[0016] S2, the crushed limestone, iron raw material, gypsum and silicon-aluminum material are measured into the raw material mill according to a given ratio through an electronic belt scale for drying and grinding to obtain a powdery material (raw material);
[0017] S3, putting the powdered material (raw material) into a new dry kiln for calcination, and obtaining clinker after cooling by a cooler;
[0018] S4, grinding the clinker to obtain the calcareous material.
[0019] Furthermore, in S2, the powdered material (raw meal) has a fineness of 0.08 mm square hole sieve residue of ≤22%.
[0020] Furthermore, in said S3, the time from entering the kiln to exiting the kiln is 30 to 45 minutes, the firing temperature of the calcining zone is 1320 to 1380° C., and the firing time of the calcining zone is 10 to 15 minutes.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention optimizes the mineral components and particularly controls the content and activity of f-CaO. At 800-900°C, CaO reacts with SiO2, Al2O3, and Fe2O3 to generate CA, C 12 A7, CF, C2F, C2S, as the sintering temperature further increases to 900-1100℃, the reaction generates C3A, C4AF, C2AS and a small amount of When the temperature rises to 1100-1200℃, a large amount of C3A, C4AF, C2S, Since the KH in the clinker is very high, the free calcium oxide is wrapped by flux minerals such as C3A, C4AF, and CaSO4, further increasing the calcination temperature, and part of the C2S further reacts to generate C3S in a certain liquid phase and a large excess of CaO. The mineral composition of the finally fired clinker meets the scope specified in the claims, and the mineral composition ratio is more beneficial to the production process and quality control of aerated concrete. It can also make the pore structure of autoclaved aerated concrete more uniform, reduce the sinking of the green body, and improve the overall quality stability. The calcareous material of the present invention has high hydration activity, fast green body hardening speed, improved production efficiency, and higher product structural strength under the condition that the dry density meets the requirements.
[0023] 2. The present invention solves the problem of unstable quality of "lime" in calcium raw materials from the perspectives of production process, equipment and clinker burning control technology through low-temperature calcination in a new dry kiln, thereby improving the utilization rate of calcium raw materials and reducing energy consumption. At the same time, by using lower-grade limestone, the efficiency of resource utilization is improved and carbon emissions are reduced to a certain extent. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0025] In the examples and comparative examples of the present invention, the chemical compositions of the raw materials used are shown in Table 1.
[0026] Table 1
[0027] raw materials <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO <![CDATA[K2O]]> <![CDATA[Na2O]]> <![CDATA[SO3]]> LOI <![CDATA[1 # Limestone]]> 2.30 0.01 1.37 52.77 0.64 0.24 0.16 0.01 42.23 <![CDATA[2 # Limestone]]> 4.26 0.53 1.27 50.64 1.08 0.50 0.10 0.02 40.98 Sulfuric acid slag 7.53 8.70 68.52 9.48 3.22 0.51 0.01 4.38 -3.52 Anhydrite 1.90 0.26 0.42 25.67 3.32 0.21 0.05 47.62 7.44 Low grade bauxite 32.90 33.03 10.98 4.16 1.21 0.51 0.07 0.12 14.05
[0028] Example 1
[0029] As a preferred embodiment of the present invention, the raw material composition of a calcium material specially used for autoclaved aerated concrete disclosed in this embodiment is shown in Table 2.
[0030] Table 2
[0031] raw materials Mass ratio / wt% limestone 93 Sulfuric acid slag 4 Anhydrite 1 Low grade bauxite 2
[0032] The preparation method of a calcium material for autoclaved aerated concrete disclosed in this embodiment is as follows:
[0033] S1. crush limestone, sulfuric acid slag, anhydrite and low-grade bauxite respectively for standby use;
[0034] S2, the crushed limestone, sulfuric acid slag, anhydrite and low-grade bauxite are measured into the raw mill according to the mass ratio corresponding to Table 2 by an electronic belt scale for drying and grinding to obtain a powdery material (raw meal);
[0035] S3, putting the powdered material (raw material) into a new dry kiln for calcination, and obtaining clinker after cooling by a cooler;
[0036] S4. Grind the calcined clinker to a surface area of 360m 2 / kg, the calcareous material of the present embodiment is obtained.
[0037] In S2, the powdery material (raw material) has a fineness of 0.08 mm and a residue on a square hole sieve of ≤22%.
[0038] In S3, the time from entering the kiln to exiting the kiln is 40 minutes, the firing temperature of the calcining zone is 1330° C., and the firing time of the calcining zone is 12 minutes.
[0039] In this embodiment, the lime used is 1 # limestone.
[0040] Example 2
[0041] As a preferred embodiment of the present invention, the raw material composition of a calcium material specially used for autoclaved aerated concrete disclosed in this embodiment is shown in Table 3.
[0042] Table 3
[0043] raw materials Mass ratio / wt% limestone 94 Sulfuric acid slag 3 Anhydrite 1 Low grade bauxite 2
[0044] The preparation method of a calcium material for autoclaved aerated concrete disclosed in this embodiment is as follows:
[0045] S1. crush limestone, sulfuric acid slag, gypsum and low-grade bauxite respectively for standby use;
[0046] S2, the crushed limestone, sulfuric acid slag, gypsum and low-grade bauxite are measured into the raw mill according to the mass ratio corresponding to Table 3 by an electronic belt scale for drying and grinding to obtain a powdery material (raw meal);
[0047] S3, putting the powdered material (raw material) into a new dry kiln for calcination, and obtaining clinker after cooling by a cooler;
[0048] S4. Grind the calcined clinker to a surface area of 355m 2 / kg, the calcareous material of the present embodiment is obtained.
[0049] In S2, the powdery material (raw material) has a fineness of 0.08 mm and a residue on a square hole sieve of ≤22%.
[0050] In S3, the time from entering the kiln to exiting the kiln is 38 minutes, the firing temperature of the calcining zone is 1360° C., and the firing time of the calcining zone is 10 minutes.
[0051] In this embodiment, the lime used is 1 # limestone.
[0052] Comparative Example 1
[0053] This comparative example is lime-free. # Limestone, and the rest are the same as in Example 1.
[0054] Comparative Example 2
[0055] This comparative example is the same as Example 1 except that the mass ratio of limestone, sulfuric acid slag, anhydrite and low-grade bauxite is 95.0wt%:1.5wt%:1.5wt%:2wt%.
[0056] Since the amount of iron raw materials added in this comparative example is small, the amount of liquid phase is small during calcination in the new dry kiln, and granulation cannot be normal. After the clinker out of the kiln enters the grate cooler, the grate cooler cannot work normally, the dust concentration in the kiln is too high, and normal production cannot be performed.
[0057] Test Example 1
[0058] The calcium materials produced by Example 1, Example 2 and Comparative Example 1 as cementitious materials are used to produce aerated concrete blocks, and the mass proportions are as follows:
[0059] Cementitious material: 14.5wt%;
[0060] Sand slurry: 59.4wt%;
[0061] Waste pulp: 26.1%wt;
[0062] The amount of aluminum powder added is 0.065wt% of the mass of the above raw materials.
[0063] Test Example 2
[0064] The calcium materials produced by using quicklime and ordinary Portland cement 42.5R as cementitious materials to produce aerated concrete blocks have the following quality proportions:
[0065] Quicklime: 9.7wt%;
[0066] Ordinary Portland cement 42.5R: 4.8wt%;
[0067] Sand slurry: 59.4wt%;
[0068] Waste pulp: 26.1wt%;
[0069] The amount of aluminum powder added is 0.065% of the mass of the above raw materials.
[0070] The static time of the aerated concrete blocks prepared in Test Example 1 and Test Example 2 was recorded, and the product appearance and product performance were tested in accordance with GB / T11968-2020 "Autoclaved Aerated Concrete Blocks" and GB / T 11969-2020 "Autoclaved Aerated Concrete Performance Test Method" as shown in Table 4.
[0071] Table 4
[0072]
[0073] It can be seen from the test data in Table 4 that the use of the calcareous material prepared in the embodiment as the gel material significantly shortens the static time and can improve the production efficiency. The mechanical properties and dry density of the product after steaming meet the quality requirements of the A3.5 B06 grade aerated concrete block, and the mechanical properties are significantly better than those of the comparative example, indicating that the calcareous material provided by the present invention can significantly improve the production efficiency of aerated concrete and improve the performance of aerated concrete.
[0074] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention to illustrate the technical solutions of the present invention, rather than limiting them, and certainly not limiting the patent scope of the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In other words, any changes or modifications made to the main design concept and spirit of the present invention that have no substantive significance, and the technical problems they solve are still consistent with the present invention, should be included in the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention in other related technical fields are also included in the patent protection scope of the present invention.
Claims
1. A calcium material specially used for autoclaved aerated concrete, characterized in that: Includes the following raw materials in mass ratio: The minerals of the calcium material include: f-CaO content of 42-55wt%, The content is 0-3wt%, the sum of C2S and C3S is 22-45wt%, the sum of C3A and C4AF is 5-20wt%, the content of periclase is 0-1.5wt%, the content of gypsum is 0-2wt%, and the content of other impurity minerals is 0-6wt%.
2. The calcareous material for autoclaved aerated concrete according to claim 1, characterized in that: The iron raw material is at least one of non-ferrous metal ash, copper slag, iron tailings, iron ore, blast furnace slag and sulfuric acid slag.
3. The calcareous material for autoclaved aerated concrete according to claim 1, characterized in that: The gypsum is at least one of dihydrate gypsum, anhydrite, desulfurized gypsum, phosphogypsum and desulfurized ash.
4. The calcareous material for autoclaved aerated concrete according to claim 1, characterized in that: The siliceous aluminum material is at least one of low-grade bauxite, aluminum smelting waste slag, aluminum tailings, and fly ash.
5. The method for preparing a calcium material for autoclaved aerated concrete according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. crush limestone, iron raw material, gypsum and silicon-aluminum material respectively for standby use; S2, the crushed limestone, iron raw material, gypsum and silicon-aluminum material are weighed according to the corresponding mass ratio, and then ground and mixed to obtain a powdery material; S3, calcining the powdered material in a new dry process kiln, and obtaining calcined clinker after cooling; S4, grinding the calcined clinker to obtain the calcareous material.
6. The method for preparing a special calcium material for autoclaved aerated concrete according to claim 5, characterized in that: In S2, the powdery material is a powder having a sieve residue fineness of ≤22% obtained by evenly passing through a 0.08 mm square hole sieve.
7. The method for preparing a special calcium material for autoclaved aerated concrete according to claim 5, characterized in that: In the S3, the time from entering the kiln to exiting the kiln is 30 to 45 minutes, the firing temperature of the calcining zone is 1320 to 1380° C., and the firing time of the calcining zone is 10 to 15 minutes.
Citation Information
Patent Citations
Modified portland cement clinker and preparation method thereof
CN107601924A
High-iron and high-silicon sulphoaluminate cement clinker prepared from molten steel slag and preparation method thereof
CN113929324A
High calcium oxide-belite cementing material as well as preparation method and application thereof
CN115611535A
Low-heat Portland cement clinker based on aerated concrete waste and preparation method thereof
CN118239703A